A case report of intersigmoid hernia treated using laparoscopic surgery - Kambe, Hiroyuki (Int J Surg Case Rep, 2021)
INTRODUCTION AND IMPORTANCE: Intersigmoid hernia (ISH) is a rare disease that is difficult to diagnose preoperatively and sometimes causes intestinal necrosis that requires emergency surgery. CASE PRESENTATION: The patient was an 87-year-old male with no history of abdominal surgery who visited our emergency outpatient service due to left lower quadrant pain and vomiting as chief complaints. Abdominal findings showed tenderness with the severest point in the left lower quadrant of the abdomen. Contrast-enhanced CT showed poor imaging of the dorsal sigmoid colon and an expanded proximal small intestine, with regional ascites around the small intestines. The patient was diagnosed with small bowel obstruction associated with ISH incarceration and underwent emergency surgery. Invagination of the small intestine into the intersigmoid fossa was found by laparoscopy. The incarcerated part was removed and the hernia orifice was sutured and closed. Mild congestion was seen in the incarcerated small intestine, but with no findings of ischemia. Thus, intestinal resection was determined to be unnecessary. The postoperative course was good and the patient was discharged on postoperative day 6. CLINICAL DISCUSSION: ISH is often diagnosed as simple ileus at the initial visit, which can result in delayed surgery. There are no case reports of complete remission of ISH with conservative therapy, and treatment with surgery is generally required. Our patient underwent early surgery because of CT findings that were characteristic of ISH and allowed diagnosis before surgery. CONCLUSION: Early diagnosis of ISH and performance of laparoscopic surgery can avoid the need for intestinal resection.